2020
DOI: 10.2987/19-6906.1
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Permethrin-Treated Military Uniforms to Protect Against a Laboratory-Maintained Knockdown-Resistant Strain of Aedes aegypti

Abstract: Military forces and the recreational industry rely on the repellent properties of permethrin-treated fabrics and N,N-diethyl-meta-toluamide (deet)–based lotions to provide protection from disease vectors and hematophagous organisms. Concerns regarding efficacy have been raised as pyrethroid resistance becomes more common and recent publications present contradictory conclusions. In this preliminary study, consenting volunteers were exposed to pyrethroid-susceptible and pyrethroid-resistant Aedes aegypti strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…This is because quantification of residual efficacy using susceptible laboratory strains is deceptive when actual exposures will be to field-resistant strains that experience insecticide selection in nature. Our result is in line with the findings of Estep et al, 59 which demonstrated that sleeves of permethrin-treated army uniform fabric failed to provide protection against the highly resistant A. aegypti.…”
Section: Discussionsupporting
confidence: 93%
“…This is because quantification of residual efficacy using susceptible laboratory strains is deceptive when actual exposures will be to field-resistant strains that experience insecticide selection in nature. Our result is in line with the findings of Estep et al, 59 which demonstrated that sleeves of permethrin-treated army uniform fabric failed to provide protection against the highly resistant A. aegypti.…”
Section: Discussionsupporting
confidence: 93%
“…Widespread prevalence of kdr mutations could severely limit the ability to control and respond to outbreaks of these diseases, as well as impact the effectiveness of permethrin-treated uniforms as originally hypothesized (Estep et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They also play a large role in the transmission of dog heartworms, a nationwide problem with approximately one million dogs affected each year (Spence Beaulieu and Reiskind 2020). Widespread prevalence of kdr mutations could severely limit the ability to control and respond to outbreaks of these diseases, as well as impact the effectiveness of permethrin-treated uniforms as originally hypothesized (Estep et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of etofenprox renders it more stable and less toxic than other pyrethroid insecticides and functions by attacking the neuronal axon of the mosquito. As concerns over the spread of pyrethroid resistance grows, and several studies of the impact of pyrethroid resistance on the protective effect treated clothing yield conflicting results [75,34,76,35] there is growing need to explore alternative insecticides for clothing treatment.…”
Section: Discussionmentioning
confidence: 99%